Kinetics and Mechanism of Oxidation of Hexamethylenediaminetetraacetatocobaltate(II) Complex by Periodate Ion in Aqueous Medium. Issue Volume 7:Issue S1(2010) (2010) - Naik, R. M.; Rai, B. Kumar J.; Rastogi, R.; Yadav, S. B. S.
Abstract : The kinetics and mechanism of oxidation of [Co II HDTA] 4- (Where HDTA=Hexamethylenediamine tetraacetic acid